2012
DOI: 10.1162/pres_a_00128
|View full text |Cite
|
Sign up to set email alerts
|

Haptic Communication to Support Biopsy Procedures Learning in Virtual Environments

Abstract: In interventional radiology, physicians require high haptic sensitivity and fine motor skills development because of the limited real-time visual feedback of the surgical site. The transfer of this type of surgical skill to novices is a challenging issue. This paper presents a study on the design of a biopsy procedure learning system. Our methodology, based on a task-centered design approach, aims to bring out new design rules for virtual learning environments. A new collaborative haptic training paradigm is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 27 publications
1
25
0
3
Order By: Relevance
“…Moreover, the subjects rated the quality of the system’s force feedback low even though they acknowledged the usefulness of haptic feedback, suggesting that the displayed haptic feedback was not appropriate. In fact, haptic feedback has been shown to be an important component for laparoscopic skill training [12, 13, 14, 15, 16, 17]. The quality of the system’s haptic feedback may have altered the users’ performance in the peg transfer task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the subjects rated the quality of the system’s force feedback low even though they acknowledged the usefulness of haptic feedback, suggesting that the displayed haptic feedback was not appropriate. In fact, haptic feedback has been shown to be an important component for laparoscopic skill training [12, 13, 14, 15, 16, 17]. The quality of the system’s haptic feedback may have altered the users’ performance in the peg transfer task.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they permit unlimited training without the expense of consumables. They can also provide haptic feedback, which has already been shown to be an essential component of minimally invasive surgery simulations [12, 13, 14, 15, 16, 17]. VR-based simulators have already been shown to transfer effective technical skills to the operating room environment [16, 18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…They are based on three-dimensional computer generated images with which the user can interact through a physical interface. Previous research has shown that virtual task trainers can actually improve intraoperative skills in minimally invasive surgery similar to that of physical task trainers (Seymour, Gallagher, Roman, O’ Bri, Andersen, & Satava, 2002; Chellali, Dumas, & Milleville-Pennel, 2012; Ullrich & Kuhlen, 2012; Yiannakopoulou, Nikiteas, Perrea, & Tsigris, 2015). …”
Section: Related Workmentioning
confidence: 98%
“…Virtual Reality (VR) technology provides a safe and versatile practice medium for teaching laparoscopic skills [10] and can overcome some limitations of the physical trainer box. For example, the VR-based systems can be used multiple times, with no need of consumables.…”
Section: Introductionmentioning
confidence: 99%
“…They provide objective and automated measurement of performance, which can improve the evaluation process [11]. Furthermore, they can be designed to provide haptic feedback, an essential component for training minimally invasive surgery skills [10, 12, 13, 14, 15, 16]. However, before introducing this technology into training curricula, there is a need to demonstrate its validity as a training tool and also as an instrument for assessing skill in laparoscopic surgery [17].…”
Section: Introductionmentioning
confidence: 99%